A Study of Problem and Awareness of Mangrove Areas in Mu Ko Chumphon National Park, Thailand - Promthep Jidapa; Phumkokrux Nutthakarn; Pattanasak Patiya; Yodying Aphittha (E3S Web of Conferences)
This study has 2 objectives: 1) to study environmental problems in all dimensions that occur in the area of Mu Ko Chumphon National Park and 2) to study the participation in protection measures, awareness, and conservation of mangrove forest resources of the people in the area of Mu Ko Chumphon National Park using field survey methods and interviews with 10 government officials and 30 people in the area. The results of the study found that the problem occurring in the mangrove forest area is encroachment on the mangrove forest area. There are in terms of making shrimp ponds, illegal logging, and including the issue of garbage floating along the mangrove trees. The conservation method is the cooperation of all parties. There are activities to plant mangrove forests every year and collect garbage to reduce any threat to the ecosystem. As a result, at present the mangrove forest area in Chumphon Islands National Park is continuously increasing.